Effects of two types of anorganic bovine bone on bone regeneration: a histological and histomorphometric study of rabbit calvaria. - Mojgan Paknejad; Amir Reza Rokn; Siamak Yaghobee; Pantea Moradinejad; Mohadeseh Heidari; Ali Mehrfard (Tehran University of Medical Sciences, 2014)
The purpose of this study was to evaluate the efficacy of two types of bone substitutes, Bio-Oss and NuOss, for repair of bone defects.This study was performed on the calvaria of 14 New Zealand rabbits. The 6mm critical size defect (CSD) models of bone regeneration were used. Three CSDs were created in each surgical site. The first defect was filled with NuOss, the second one with Bio-Oss and the third one remained unfilled as the control. After healing periods of one and two months (seven animal for each time point), histological and histomorphometric analyses were carried out to assess the amount of new bone formation, presence of inflammation, foreign body reaction and type of new bone. Qualitative variables were analyzed by multiple comparisons, Wilcoxon, Friedman and Mann Whitney tests. Quantitative variables were analyzed using the Mann-Whitney and Wilcoxon tests. Level of statistical significance was set at 0.05.The level of inflammation was not significantly different at four and eight weeks in the Bio-Oss (P=0.944), NuOss (P=1.000) and control groups (P=0.71). At four weeks, foreign body reaction was not observed in Bio-Oss, NuOss and control groups. There was no significant difference in the type of the newly formed bone at four and eight weeks in any group (P=0.141 for Bio-Oss, P=0.06 for NuOss and P=0.389 for the control group).Deproteinized bovine bone mineral can be used as a scaffold in bone defects to induce bone regeneration.